2019
DOI: 10.1161/circoutcomes.118.005624
|View full text |Cite
|
Sign up to set email alerts
|

Clinic-Based Strategies to Reach United States Million Hearts 2022 Blood Pressure Control Goals

Abstract: Background-The Centers for Disease Control and Prevention's Million Hearts initiative includes an ambitious ≥80% blood pressure control goal in U.S. adults with hypertension by 2022. We used the validated Blood Pressure Control Model (BPCM) to quantify changes in clinic-based hypertension management processes needed to attain ≥80% blood pressure control.Methods and Results-The BPCM simulates patient blood pressures weekly using three key modifiable hypertension management processes: office visit frequency, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 49 publications
1
39
0
2
Order By: Relevance
“…Therapeutic inertia has been identified as a key clinician-level barrier to BP control. 13 , 27 , 28 , 29 A simulation by Bellows et al 30 found that medication intensification was the most influential of the multiple interventions to achieve BP control. In community practice, therapeutic inertia is estimated to be present in more than 80% of clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic inertia has been identified as a key clinician-level barrier to BP control. 13 , 27 , 28 , 29 A simulation by Bellows et al 30 found that medication intensification was the most influential of the multiple interventions to achieve BP control. In community practice, therapeutic inertia is estimated to be present in more than 80% of clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“… 31 An analysis by Bellows et al found that, out of the multiple interventions to achieve BP control, medication intensification was the most impactful. 32 …”
Section: Key Themes That Emerged From the Conversationmentioning
confidence: 99%
“… 42 , 43 To do so, we must invest in increasing the implementation of and providing greater access to proven highly effective team‐based care models for hypertension. 32 , 33 We have a steep climb ahead. A recent report found that 40% of patients with uncontrolled hypertension are only taking one antihypertensive medication.…”
Section: Next Steps To Make Progressmentioning
confidence: 99%
“…Beyond logistics, integrating more-intensive BP goals into clinical practice will be challenging at the prescriber level. Clinical inertia, the phenomenon of not initiating or intensifying therapy at the point of care despite a BP reading that is above goal, is highly prevalent in hypertension management [43,44] and may be a key factor preventing BP control [45]. Several factors associated with the patient, provider, and system elicit clinical inertia [46], such as low health literacy, insufficient provider-patient time, or lack of protocols.…”
Section: Opportunities and Challengesmentioning
confidence: 99%